(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background- Management of complex and chronic wounds remains a major surgical challenge, particularly in resource-limited settings. Although VAC (Vacuum-Assisted Closure) therapy has demonstrated superior wound healing outcomes compared to conventional dressings, the high cost of commercial systems limits widespread use. This study evaluates the efficacy of an innovative, indigenously modified vacuum-assisted wound closure technique using locally available materials compared to conventional dressing in wound management. Methods- A prospective case-control study was conducted in the Department of General Surgery at Karnataka Institute of Medical Sciences (KIMS), Hubballi, over 24 months. A total of 80 patients aged 18–70 years were enrolled and divided into two equal groups: The control group (n=40) received conventional dressings, and the experimental group (n=40) received modified VAC therapy using autoclaved sponge, suction catheter, and locally available vacuum devices (portable suction, syringe, or Romovac). Parameters assessed included wound area, wound score, number of debridements, frequency of dressing changes, hospital stay, pain score (VAS), microbiological culture, complications, and mode of healing. Statistical analysis was performed using appropriate tests, with p<0.05 considered significant. Results- Both groups were comparable at baseline (p>0.05). The experimental group showed significantly greater reduction in wound area (111.23 ± 64.29 cm² vs. 141.18 ± 19.43 cm²; p=0.006) and lower final wound score (6.55 ± 2.30 vs. 8.60 ± 2.06; p<0.001). The number of debridements (1.35 ± 1.39 vs. 2.85 ± 1.41; p<0.001), frequency of dressing changes (10.23 ± 4.57 vs. 26.85 ± 10.27; p<0.001), and hospital stay (31.83 ± 11.98 days vs. 38.55 ± 14.30 days; p=0.025) were significantly lower in the experimental group. Pain scores were comparable (p=0.451). By the third culture, “No Growth” was observed in 60% of experimental patients compared to 40% in controls. Complications were minimal. Conclusion- The indigenously modified vacuum-assisted wound closure technique is significantly superior to conventional dressing in promoting wound healing, reducing dressing frequency, minimizing debridements, and shortening hospital stay. It is a safe, effective, and cost-efficient alternative suitable for resource-constrained settings.